The binding of key fishy off-flavor compounds to silver carp proteins: a thermodynamic analysis. Issue 19 (19th March 2020) - Gu, Saiqi; Dai, Wangli; Chong, Yunqing; Lyu, Fei; Zhou, Xuxia; Ding, Yuting
Abstract : Myosin was shown to be the primary binding receptor of the four KFOCs and showed the strongest binding under neutral pH and high ionic strength. Its affinity for 1-octen-3-ol was the highest. Abstract : The binding of key fishy off-flavor compounds (KFOCs), heptanal, octanal, nonanal, and 1-octen-3-ol, to silver carp proteins (total myofibrillar protein, myosin, and actin) was studied. Myosin was the primary binding receptor for all four KFOCs, and it showed the strongest binding at neutral pH and at higher ionic strengths. Thermodynamic models were applied to evaluate the number of binding sites, the binding constant, and the Gibbs free energy for the binding of the KFOCs to myosin. Myosin had approximately 1.0 sites for binding with the three linear-chain aldehydes and about 1.6 sites for binding with 1-octen-3-ol. Moreover, myosin showed the highest affinity for 1-octen-3-ol, and both its binding constant and its number of binding sites with the three linear-chain aldehydes were negatively correlated with the chain length. For all four KFOCs, the trends of the Gibbs free energies were the opposite of those observed for the binding constant and the number of binding sites. These results may provide a theoretical basis for improving the deodorization efficiency of traditional surimi rinsing methods by adjusting the properties of the solutions used.